Oromský nacionalismus v čase nejednoty - Jan Záhořík (AntropoWebzin)
This study deals with the politically sensitive but very topical conterporary issue of the Oromo nationalism which forms an important part of the modern history of Ethiopia. Recent developments in Ethiopia, as well as among the Oromo diaspora, show that there exists a huge diversity within the so-called Oromo nationalism which makes it very complicated to describe and analyze the movement in general. The main claim of this article is that rather than one unified Oromo nationalism, there are various types of Oromo nationalism which are in many cases mutually unintelligible. Moreover, contemporary Oromo historiography has become so much influenced by simplifications and mythologization that it is almost impossible to lead a serious discussion about specific historical issues regarding the Oromo population in Ethiopia. This article is a modest contribution to understanding the complexity of Ethiopian socio-political development, as well as to the issue of Oromo nationalism in particular.